You are on page 1of 3

# Math 415 Spring 2011 Homework 6 Solutions

Sec 4.1, No 5: Determine whether the following are linear transformations from R3 into R2 :

## (a) L(x) = (x2 , x3 )T

Solution:
L(x + y) = L((x1 + y1 , x2 + y2 , x3 + y3 )T )
= (x2 + y2 , x3 + y3 )T
= (x2 , x3 )T + (y2 , y3 )T
= L(x) + L(y)
so this one is linear

## (b) L(x) = (0, 0)T

Solution:
L(x + y) = L((x1 + y1 , x2 + y2 , x3 + y3 )T )
= (0, 0)T
= (0, 0)T + (0, 0)T
= L(x) + L(y)
so this one is linear

(c) L(x) = (1 + x1 , x2 )T

Solution: Since linearity implies, in particular, that L(x) = L(x), if we set = 0 we see that
L(0) = 0. But for the L we are given we see that L(0) = (1, 0)T 6= (0, 0)T , so this one is not linear.

## (d) L(x) = (x3 , x1 + x2 )T

Solution:
L(x + y) = L((x1 + y1 , x2 + y2 , x3 + y3 )T )
= (x3 + y3 , (x1 + y1 ) + (x2 + y2 ))T
= (x3 + y3 , (x1 + x2 ) + (y1 + y2 ))T
= (x3 , x1 + x2 )T + (y3 , y1 + y2 )T
= L(x) + L(y)
so this one is linear

Sec 4.2, No 3: For each of the following linear operators L on R3 , find a matrix A such that
L(x) = Ax for every x in R3 :

## Solution: The matrix we need has columns

a1 = L(e1 ) = L((1, 0, 0)T ) = (0, 0, 1)T
a2 = L(e2 ) = L((0, 1, 0)T ) = (0, 1, 0)T
a3 = L(e3 ) = L((0, 0, 1)T ) = (1, 0, 0)T
so

0 0 1
A= 0 1 0
1 0 0

0 0 1 x1 x3
Check Ax = 0 1 0 x2 = x2 = L(x)
1 0 0 x3 x1

## a1 = L(e1 ) = L((1, 0, 0)T ) = (1, 1, 1)T

a2 = L(e2 ) = L((0, 1, 0)T ) = (0, 1, 1)T
a3 = L(e3 ) = L((0, 0, 1)T ) = (0, 0, 1)T

so

1 0 0
A= 1 1 0
1 1 1

1 0 0 x1 x1
Check Ax = 1 1 0 x2 = x1 + x2 = L(x)
1 1 1 x3 x1 + x2 + x3

## a1 = L(e1 ) = L((1, 0, 0)T ) = (0, 3, 2)T

a2 = L(e2 ) = L((0, 1, 0)T ) = (0, 1, 0)T
a3 = L(e3 ) = L((0, 0, 1)T ) = (2, 0, 1)T

so

0 0 2
A= 3 1 0
2 0 1

0 0 2 x1 2x3
Check Ax = 3 1 0 x2 = 3x1 + x2 = L(x)
2 0 1 x3 2x1 x3

## Sec 4.2, No 13: Let L be the linear mapping of P2 into R2 defined by

 R1 
p(x)dx
L(p(x)) = 0
p(0)
Find a matrix A such that  

L( + x) = A

## Solution: Take as a basis of P2 the polynomials p1 (x) = 1, p2 (x) = x. Then we compute

 R1   R1   
p 1 (x)dx dx 1
a1 = L(p1 ) = 0 = 0 =
p1 (0) 1 1
 R1   R1   1 
0 2
p (x)dx xdx 2
a2 = L(p2 ) == = 0 =
p2 (0) 0 0

1 12
 
A=
1 0
1 12 + 12
      

Check A = =
1 0
 R1   1

( + x)dx + 2

L( + x) = 0 =
( + x)|x=0